Detection of both Type 1 and Type 2 Plasminogen Activator Inhibitors in Human Monocytes - Castellote, Joan C; Grau, Enric; Linde, Maria A; Pujol-Moix, Nuria; Rutllant, Miquel LI (Thrombosis and Haemostasis, 1990)
Increasing evidence suggests the involvement of leukocytes in the fibrinolytic system. Monocytes secrete pro-urokinase (Grau, Thromb Res 1989; 53: 145) and it has been shown that these cells have specific receptors for urokinase and plasminogen (Miles, Thromb Haemostas 1987; 58: 936). The aim of this study was to analyse the presence of plasminogen activator inhibitor(s) in platelet-free suspensions of human peripheral blood monocytes and polymorphonuclear leukocytes (PMN). SDS-PAGE and reverse fibrin autography showed an inhibitory band of 50 kDa in the monocyte extracts (Triton X-100) but not in the PMN extracts. Urokinase (u-PA) was mixed with increasing amounts of monocyte extract for 10 min and the mixtures were added to 125Ifibrin coated wells containing plasminogen. A dose-dependent decrease in the u-PA fibrinolytic activity was observed. The amount of inhibition increased when the monocyte releasates were preincubated with u-PA (40% inhibition after 5 min preincubation and 80% after 15 min), indicating a direct interaction between this activator and an inhibitor(s). After SDS-PAGE of monocyte extracts, immunoblotting and peroxidase staining identified both PAI1 and PAI2, with an apparent molecular weight of 47-50 kDa. Monocyte-associated PAI1 formed complexes with single chain t-PA with a molecular mass 50 kDa higher than the molecular mass of the free PAI1. However, a significant amount of PAI remained unbound to t-PA. This inactive PAI1 could have come from a rapid inactivation of the primary active PAI1. These PAI1 and PAI2 detected in human monocytes may be transcendent in the regulation of the fibrinolytic system.
Keywords: Fibrinolysis; Plasminogen activator inhibitor; Monocytes; Polymorphonuclear leukocytes; Immunoblotting